Leadership Education for College and Career Readiness: The CAMP Osprey Mentoring Program - Matthew Ohlson (The University of Alabama, 2022)
This article describes a program that combines meaningful community-based experiential learning for collegiate students with leadership-based mentoring, delivered either face-to-face or virtually, that helps K-12 students see college as an option for their future. The CAMP (Collegiate Achievement Mentoring Program) model is a partnership between institutions of higher education and K-12 schools, in which collegiate student mentors are paired with children in high-poverty K-12 schools to improve leadership and career-readiness skills for collegiate mentors and leadership and college-readiness skills for mentees. The CAMP model has positively impacted the academic and social outcomes of more than 1,500 student mentors and mentees in four states. This article describes the genesis, development, process, and outcomes of the CAMP Osprey program at the University of North Florida as a model for other educational institutions to replicate and adapt to meet the needs of their students. The program is readily replicable and is notable among mentoring models because it is based on leadership development and can be delivered virtually.